Racial/ethnic differences in health-related quality of life among female breast cancer survivors: cross-sectional findings from the Medical Expenditure Panel Survey. (July 2021) - Jackson, I.; Rowan, P.; Padhye, N.; Hwang, L.Y.; Vernon, S.W.
Abstract: Objectives: Breast cancer survivors have reported worse health-related quality of life (HRQoL) outcomes on some subscales when compared with members of the general population. However, the increased attention to breast cancer survivorship should have improved the HRQoL of these survivors. Our aim was to examine whether physical and mental component scores (PCS-12 and MCS-12) using the Short Form (SF-12) questionnaire were different for racial/ethnic minorities, specifically for Black and Hispanic women relative to White women. Furthermore, we stratified the data by age group to evaluate these racial/ethnic differences in HRQoL of breast cancer survivors. Study design: Cross-sectional study. Methods: Pooled cross-sectional analyses using data from the Medical Expenditure Panel Survey between 2008 and 2016 were conducted. Pooled ordinary least squares (OLS) regression was used to examine the racial/ethnic differences in PCS-12 and MCS-12 scores of breast cancer survivors. Furthermore, stratified analyses by age group were conducted to evaluate racial/ethnic differences in HRQoL by the age of breast cancer survivors. Results: After adjusting for confounders, there was no association between race/ethnicity and PCS-12 scores. However, Hispanic breast cancer survivors had statistically significantly lower MCS-12 scores (by 1.9 points [95% confidence interval CI: −3.53 to −0.37]) when compared with White breast cancer survivors. For PCS-12, after stratifying by age, the adjusted analyses showed no significant differences in PCS-12 scores when White female breast cancer survivors were compared with the other racial/ethnic categories. On the other hand, Black female survivors aged <50 years had 4.3 points (95% CI: 0.46–8.13) higher MCS-12 scores when compared with their White counterparts, while Hispanic breast cancer survivors aged <50 years had 3.1 points (95% CI: −0.40–6.69) higher MCS-12 scores relative to White women. Furthermore, among female breast cancer survivors aged ≥50 years, Hispanic women had 3.2 points (95% CI: −4.98 to −1.40) lower MCS-12 scores than White women. Conclusion: Our study generated findings showing the racial/ethnic differences in HRQoL of breast cancer survivors and presented results stratified by age group. These findings provide the much-needed rationale for targeted and racial/ethnic-specific HRQoL improvement strategies among breast cancer survivors.